Die taak van die bestuurder - Arangies, J. (Koers, 1987)
The aim with the article is to approach the task of the manager from a Scriptural perspective. The need for the giving of guidance is as old as mankind itself, and examples of managers, thus management, are found throughout Scripture. Management is a process by means of which an attempt is made to use human and other resources as optimally as possible in order to provide in certain needs and to attain certain objectives.